Radiation hard multi-strip multi-gap resistive plate chamber architecture for low polar angles of the CBM-TOF wall - Petriş, Mariana; Aprodu, V.; Deppner, I.; Duţă, V.; Frühauf, J.; Herrmann, Norbert; Petrovici, M.; Radu, A.; Rubio, Esteban (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2025)
For the mitigation of the gas pollution effects in Multistrip Multigap Resistive Plate Chambers (MSMGRPCs) exposed to high irradiation doses, prototypes with a direct flow of the gas mixture through the gas gaps and discrete polyimide spacers were designed and assembled. The aging investigations of the chambers with the new design demonstrated negligible aging effects even for rather low gas flow rate. Two such prototypes were tested in real operation conditions, in an in-beam test performed at the SIS18 accelerator of GSI Darmstadt with reaction products. The obtained results are reported in this paper. They demonstrate the performance of the prototypes in terms of efficiency (>95%) and time resolution (∼55 ps). Therefore, such direct flow MSMGRPCs will be implemented in the modular configuration of the low polar angle region of the CBM-TOF wall, called inner wall. Among the 12 modules of the CBM-TOF inner wall, the M0 module has the most complex structure. Details about the implementation of the direct flow MSMGRPCs of different granularities in the M0 module, whose assembling is in progress, are presented.